2020
DOI: 10.2499/p15738coll2.133811
|View full text |Cite
|
Sign up to set email alerts
|

National extension policy and state-level implementation: The case of Cross River State, Nigeria

Abstract: The International Food Policy Research Institute (IFPRI), a CGIAR Research Center established in 1975, provides evidence-based policy solutions to sustainably end hunger and malnutrition and reduce poverty. The Institute conducts research, communicates results, optimizes partnerships, and builds capacity to ensure sustainable food production, promote healthy food systems, improve markets and trade, transform agriculture, build resilience, and strengthen institutions and governance. Gender is considered in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The result shows that less than one-tenth of the youth who are intensively involved in agriculture have access to extension and advisory services. The findings of our study are congruent with those from studies [53,54] examining the linkages between youth in agriculture and access to extension and advisory services.…”
Section: Summary Of Statisticssupporting
confidence: 90%
“…The result shows that less than one-tenth of the youth who are intensively involved in agriculture have access to extension and advisory services. The findings of our study are congruent with those from studies [53,54] examining the linkages between youth in agriculture and access to extension and advisory services.…”
Section: Summary Of Statisticssupporting
confidence: 90%
“…However, several factors influence the decision of youths to engage in off-farm employment and to determine the type of jobs they engage in. References [4,[17][18][19] revealed that due to restricted opportunities in rural areas, desperate youths going into off-farm work choose low-paying, unskilled off-farm wage employment to earn a living [4,[18][19][20]. The low employment opportunities for youths in rural areas have been related to the underdevelopment and poor access to economic resources [21].…”
Section: Nigerian Youth Employment and Sustainable Development Policiesmentioning
confidence: 99%
“…Agriculture persists as the main employer of labor in the rural areas in Sub-Saharan Africa (SSA). In Nigeria, about 70% of the youth-dominated labor force lives in rural areas and only very few of them work in the non-farm sector as well as in small and medium-scale enterprises that depend directly or indirectly on agriculture [1][2][3][4]. While their employment status may be seasonal or casual, the majority of the rural youths earn very low income/wages while they work under unfavorable and unsafe working conditions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, in Nigeria, there has been a growing concern for the provision of quality, efficient and sustainable agricultural extension services to majority of farmers who are responsible for the bulk of agricultural production (Oguniyi et al, 2020). Extension practitioners are said to be unresponsive to farmers' need, unaccountable for services rendered, not liable for unethical conduct, prone to incorrect and wrong message dissemination and general inefficient service delivery.…”
Section: Introductionmentioning
confidence: 99%